Guide for the determination of thermal endurance properties of electrical insulating materials. Instructions for calculating thermal endurance characteristics. Calculations for incomplete data: proof test results up to and including the median time to end-point (equal test groups) Part 3-2, (15th December 1995) - British Standards Institution,
No abstract available